2014
DOI: 10.1159/000354118
|View full text |Cite
|
Sign up to set email alerts
|

Improving Topical Non-Melanoma Skin Cancer Treatment: In vitro Efficacy of a Novel Guanosine-Analog Phosphonate

Abstract: Actinic keratosis, a frequent carcinoma in situ of non-melanoma skin cancer (NMSC), can transform into life-threatening cutaneous squamous cell carcinoma. Current treatment is limited due to low complete clearance rates and asks for novel therapeutic concepts; the novel purine nucleotide analogue OxBu may be an option. In order to enhance skin penetration, solid lipid nanoparticles (SLN, 136-156 nm) were produced with an OxBu entrapment efficiency of 96.5 ± 0.1%. For improved preclinical evaluation, we combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Hoeller Obrigkeit and colleagues use low carcinoma cell counts [16], Commandeur et al seed carcinoma cells only [15], and we used previously a ratio of 3:100 carcinoma to normal cells [11,18]. Albeit their limitations, carcinoma cell lines are Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hoeller Obrigkeit and colleagues use low carcinoma cell counts [16], Commandeur et al seed carcinoma cells only [15], and we used previously a ratio of 3:100 carcinoma to normal cells [11,18]. Albeit their limitations, carcinoma cell lines are Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since organotypic NMSC models are developed for preclinical drug evaluation [11,15,16], we investigated the response of cSCC-E and cSCC-ED models to ingenol mebutate in a blinded vehicle-controlled study design (Fig. 4A).…”
Section: Ingenol Mebutate Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Gosselin et al [34] reported a 2′-C-methyl branched guanosine pro-nucleotide as a potent liver-targeted HCV polymerase inhibitor. Schaefer–Korting et al [35] found that a guanosine-analog phosphonate can improve topical non-melanoma skin cancer treatment.…”
Section: Introductionmentioning
confidence: 99%